PELAKSANAAN PELAYANAN TERHADAP KEPUASAN NASABAH PT. BANK BUKOPIN TBK. PEKANBARU - Nico Partawijaya; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this study was to determine how the effect of the implementation of the services carried out by PT. Bank Bukopin. Pekanbaru on customer satisfaction is one of the private banking firm of commercial enough in the eyes of Indonesian society, especially citizens pekanbaru. PT. Bank Bukopin have to apply the implementation of services to its customers to cause satisfaction to its customers which would cause annoyance want to use banking services on a continuous basis Bank Bukopin. In this case the optimal performance of employees and work in accordance with the standards of the company will be able to realize the objectives of the company. In this study, the population is Bukopin customers as many as 100 people by distributing a questionnaire and interviews. The study concluded that implementation of the service effect on customer satisfaction in PT. Bank Bukopin. Pekanbaru. With evidence of regression calculation results showed that t calculate is greater than t table is t calculate (4.447)> t table (1.985) and Sig. (0,000) <0.05.Keywords: Service Implementation and Customer Satisfaction